LPI Radar Signal Design Resistant to Identification by ESM Systems - Liu, Xinyu; Yuan, Ye; Zhang, Tianxian; Cui, Guolong; Tay, Wee Peng (IEEE transactions on aerospace and electronic systems, 2023)
We consider the design of a low probability of intercept (LPI) radar signal that is resistant to identification by an electronic support measure (ESM) system. We assume that the ESM attempts to distinguish between radar signal types in a finite set. A multihypothesis testing Bayesian decision framework is formulated, in which a feature mapping is optimized to map the radar signal at the radar transmitter to maximize the Bayesian identification error probability of the ESM, subject to radar system cost constraints. This optimization problem is, however, intractable in general. We utilize a successive lower bound minimization approach to modify the problem and a sequential iterative technique with a polynomial complexity to obtain the feature mapping results. Numerical simulations demonstrate the effectiveness of the LPI signal design algorithm.